Համիդեան կոտորածները Տրապիզոնում 1895 ին - Յակոբեան, Նարինէ Ս. (տպ. Atlas)
The article focuses on the anti -Armenian policy of the Ottoman Empire in the province of Trapizon during the Hamidian massacres. Drawing on primary sources, it examines the massacres of Armenians in the region and the persecutions they faced. Specifically, the article analyzes the involvement of the state, local authorities, and various groups in organizing and carrying out these atrocities, as well as the consequences of the massacres. A detailed analysis of the primary sources reveals that, from October to December 1895, Turkish authorities executed massacres and looting in the province of Trabzon, with the highest inte nsity occurring in the city of Trabzon and the surrounding villages. Local authorities, regular army units, police forces, and irregular detachments composed of local Muslims actively participated in these massacres. Additionally, there were instances of f orced conversion to Islam.
Keywords: Պատմութիւն; Հայ Ցեղասպանութիւն; Տրապիզոն